2013
DOI: 10.1021/es401958u
|View full text |Cite
|
Sign up to set email alerts
|

Poly-Use Multi-Level Sampling System for Soil-Gas Transport Analysis in the Vadose Zone

Abstract: Soil-gas turnover is important in the global cycling of greenhouse gases. The analysis of soil-gas profiles provides quantitative information on below-ground turnover and fluxes. We developed a poly-use multi-level sampling system (PMLS) for soil-gas sampling, water-content and temperature measurement with high depth resolution and minimal soil disturbance. It is based on perforated access tubes (ATs) permanently installed in the soil. A multi-level sampler allows extraction of soil-gas samples from 20 locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Subatmospheric CH 4 concentrations from siliceous sites showed that the SR did not "generate" CH 4 by an unknown mechanism. Furthermore, we are confident that sampling with the MLS reflected steady-state situations, as suggested by various tests with the instrument (Nauer et al, 2013). Using the MLS the soil is not disturbed during sampling through access Fig.…”
Section: Comparison Of Mls and Sr Profilessupporting
confidence: 54%
See 2 more Smart Citations
“…Subatmospheric CH 4 concentrations from siliceous sites showed that the SR did not "generate" CH 4 by an unknown mechanism. Furthermore, we are confident that sampling with the MLS reflected steady-state situations, as suggested by various tests with the instrument (Nauer et al, 2013). Using the MLS the soil is not disturbed during sampling through access Fig.…”
Section: Comparison Of Mls and Sr Profilessupporting
confidence: 54%
“…Collection of soil-gas samples was accomplished using the SR (Nauer et al, 2012) and the MLS as part of a newly developed sampling system (Nauer et al, 2013). A graphical overview of both instruments is given in the supporting information.…”
Section: Soil-gas Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…At locations A to C, we employed the soil gas profile method to determine soil-atmosphere CH 4 flux (milligrams of CH 4 per square meter per day) (e.g., see reference 19). To this end, depth-resolved soil gas samples were collected using a polyuse multilevel sampling system (61). Details of the installation, sampling, and measurement procedures were described previously (54).…”
Section: Methodsmentioning
confidence: 99%
“…Petersen. E-mail: soren.o.petersen@agrsci.dk Received 26 February 2014; revised version accepted 24 June 2014 gas from sub-surface sampling positions via nylon tubing (Rolston et al, 1976), stainless steel tubing (Park et al, 2011;Petersen et al, 2011) or more advanced probe designs (Nauer et al, 2013). Disturbance of soil gas distribution during sampling can be avoided by sampling from a diffusion cell in contact with the surrounding soil with a gas-permeable membrane of polytetrafluoroethylene (Magnusson, 1989), polyethylene (DeSutter et al, 2006), polypropylene (Gut et al, 1998) or silicone (Dörr & Münnich, 1980;Thomas & Lloyd, 1995;Panikov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%